Pengaruh Free Cash Flow, Kebijakan Hutang dan Profitabilitas terhadap Kebijakan Dividen pada Perusahaan Sektor Perbankan yang Tercatat di BEI Tahun 2019-2023 - Muhlis, Fatkur; Sam, Iskandar; Tiswiyanti, Wiwik (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to: (1) To see the effect of free cash flow, debt policy and profitability on dividend policy in banking sector companies listed on the IDX in 2019-2023. (2) To see the effect of free cash flow on dividend policy in banking sector companies listed on the IDX in 2019-2023. (3) To see the effect of debt policy on dividend policy in banking sector companies listed on the IDX in 2019-2023. (4) To see the effect of profitability on dividend policy in banking sector companies listed on the IDX in 2019-2023. This study uses a quantitative approach with a descriptive statistical research type. Based on this study, it can be concluded that Based on the research findings, it can be concluded that: first, the variables free cash flow (fcf), debt policy, and profitability simultaneously affect dividend policy, in accordance with the research of Kresna & Ardini (2020) and Aditya Sidharta & Nariman (2021). Second, fcf does not affect dividend policy, because companies tend to allocate their funds for company development rather than distributing dividends. Third, the debt policy variable (DER) has a positive effect on dividend policy partially, which means that the higher the company's debt level, the greater the dividend given. Fourth, the profitability variable also has a positive effect on dividend policy, where the greater the profit obtained by the company, the greater the dividend distributed to shareholders.